0240 Investigating the Potential for Actigraphy as a Complementary Clinical Tool for Evaluation of Sleep in Patients with Rheumatoid Arthritis. (25th May 2022) - Rader, Shelby; Cox, Ava; Weeks, Anna; Stratton, Jeanine; Merchant, Gulzar; Cozad, Melanie; Fowler, Lauren
Abstract: Introduction: Poor sleep is a common complaint among patients with rheumatoid arthritis (RA), but few actively recognize the problem or discuss it with their rheumatologist during the clinical visit. Challenges to identification of sleep issues include a lack of standardized sleep measures used within clinical care and lack of confidence on the part of patients' articulating how sleep is affected by RA. Clinical management is further complicated by insufficient evidence between sleep quality and disease symptomology. The objective of this study was to identify correlations between sleep measures assessed through self-report and actigraphy with disease activity for patients with RA. Methods: In a prospective, cross-sectional study, a sample of 15 participants diagnosed with RA were recruited through convenience sampling. Consenting participants self-reported sleep quality and disease activity using Pittsburgh Sleep Quality Index (PSQI) and Routine Assessment of Patient Index Data 3 (RAPID-3). Participants' sleep quality was also measured using actigraphy which monitors wrist movement by wearing a watch. Daily actigraphy measures of sleep efficiency, latency, and fragmentation were averaged over 6 nights. Actigraphy measures were correlated to the PSQI and RAPID-3 through Spearman correlations. Results: The sample was mostly Caucasian women with an average age of 55 years, generally reflective of the population with RA. The results demonstrated weak, nonsignificant correlations between self-reported measures of sleep and average sleep efficiency (0.12, p=0.66), latency (0.10, p=0.72), and fragmentation (-0.13, p=10). Additionally, weak, nonsignificant correlations existed between disease activity and average sleep efficiency (0.09, p=0.75), latency (0.35, p=0.19), and fragmentation (-0.12, p=65). Conclusion: This study's implications suggest actigraphy may provide complementary information to self-reported measures of sleep. Such information may support patients' articulation of sleep issues to the rheumatologist. Further research is necessary to understand how actigraphy measures can be effectively summarized for use by the patient and rheumatologist to discuss sleep issues during the clinical encounter as well as their ability to support clinical diagnosis of sleep disorders. Support (If Any): Support: Prisma Health Upstate Seed Grant 2019-2020. University of South Carolina Magellan Scholar & Apprentice Programs funding Shelby Rader. Furman University Center for Engaged Learning for summer internship funding for Ava Cox.